Safety and efficacy of flow diverter stents in the treatment of bifurcation cerebral aneurysms: single-center experience - Yerbol Makhambetov; Aiman Maidan; Chingiz Nurimanov; Assylbek Kaliyev; Baurzhan Kunakbayev; Nurtay Nurakay; Serik Dyussembayev; Nursultan Makhambetov (Diagnostic and Interventional Radiology)
PURPOSE: The use of flow diverter (FD) stents is continually expanding. Aneurysms on arterial bifurcation typically have an undesirable anatomical form, are frequently wide-necked, and include one or more side-branch arteries. In recent years, the off-label use of flow diversion in treating intracranial aneurysms beyond the internal carotid artery has become increasingly popular. This study reports our center’s initial experience treating bifurcation aneurysms with FD devices, documenting occlusion outcomes using the O’Kelly–Marotta and modified Cekirge–Saatci scales, as well as the safety of FD usage in bifurcation locations. METHODS: This retrospective, single-center study analyzed a prospectively maintained database of patients with cerebral aneurysms treated endovascularly. The study identified bifurcation aneurysms that were treated between January 2019 and May 2022 by placing an FD device covering the neck of the aneurysm. RESULTS: Our short series suggests that flow diversion is a viable therapeutic option for bifurcation aneurysms with favorable angiographic outcomes. CONCLUSION: In highly selective cases, flow diversion may be considered for treating bifurcation aneurysms in patients who will undergo follow-up examinations in the future. CLINICAL SIGNIFICANCE: Flow diversion has emerged as a valuable technique in the management of bifurcation aneurysms, offering the potential for satisfactory occlusion and long-term outcomes.